Regulating the urban commons - Vrabie, Anamaria (Central European Public Administration Review, 2020)
This paper examines the effect of build environment regulations for facades emergency repairs and embellishment, as implemented by the city of Cluj-Napoca, the second largest municipality in Romania. The scope was to identify to what extent the over taxation measure was efficient in generating compliant behaviour and what secondary effects it may have generated in people's attitude towards the local authorities. We conducted structured interviews with 25 homeowners targeted by the policy. The qualitative analysis uncovers structural issues on how the policy was implemented and communicated to the population. It further acknowledges difficulties in managing mixed property and collective actions. We interpret the findings as a first step towards building a more comprehensive research framework focused also on included behavioural insights, as captured by our recommendations. Namely, they illustrate that homeowners were critical about the measure, both in its rationale and its implementation, and were unable to act upon a cost-benefit analysis given the ambiguous available information. The findings further acknowledge difficulties in managing mixed property and collective actions, but they also hint favourably towards the role of peer effects, expressed here as compliant neighbours' behaviour. We interpret the results of this exploratory case study as a first step towards building a more comprehensive approach to serve as a toolkit in examining the development of innovative local policies in post-communist environments, through a combined research framework including also the significant contribution of behavioural insights, next to the traditional rational actor theories. Naturally, the usual limitations of the method also apply to our study, in the sense of non-generalizable conclusions. This fuels up the need for further research on similar regional and urban challenges in an extended multiple-case study scheme.
Keywords: behavioural insights; building facades; compliant behaviour; fasade; lokalne politike; obnavljanje stavb; policy design; predpisi; regulation; Romania; Romunija